Metabolic dysfunctions and dynamic of antioxidant enzymes activity in developing recalcitrant cacao (Theobroma cacao) seeds at different storage conditions - Shahruddin, Shafeeqa; Awang, Azwan; Azman, Elisa Azura; Abu Kassim, Faizah (Universiti Putra Malaysia, 2025)
A potential breakthrough in improving the short-term preservation of recalcitrant cacao (Theobroma cacao) seeds is the specific conditions with slow-drying procedures. Thus, this study aimed to elucidate the effect of storage conditions on the physio-chemical and reactive oxygen species (ROS) antioxidant enzymes with slow-drying processes in cacao seeds. Seeds from ripened cacao pods (clone PBC 123) were demucilaged, placed in a zip-lock polyethene bag, and stored at 14°C and 16°C (40% and 80% relative humidity [RH]), room temperature (RT; 25°C), and control (0 days of storage). Seeds at 14°C tend to retain the highest respiration rate during 12 days of storage. Their impaired respiratory activity is reflected through the highest accumulation of soluble sugar during the first 6 days after storage, lower protein content with the highest antioxidant enzyme activities, indicating increased ROS production. Antioxidant enzymes involved in the glutathione-ascorbate cycle, ascorbate peroxidase, and glutathione reductase activity were crucially responsive to the oxidative status within seed cells at 14°C. In contrast, seeds demonstrated decreasing moisture content during storage (RT and 16°C, 40% RH). They displayed higher ROS (hydrogen peroxide) signalling but within the oxidative concentration threshold, giving the advantage of holding seeds with lesser exposure to oxidative stress. As the condition of 16°C, 40% RH produced lesser germinated seeds (8% to 12%) than seeds at RT during storage, it is then suggested to be the alternative to minimise seed’s physio-chemical changes, contributing to the maximum germination characteristics for 12 days of storage, and thus, increase the potential for further exploration.